Simultaneous occurrence of non-Hodgkin lymphoma, renal cell carcinoma and oncocytoma: A case report - Zabrocka, Ewa (Mol Clin Oncol, 2016)
We herein report the case of a 74 year-old woman with a diffuse large B-cell lymphoma and bilateral renal masses identified on computed tomography scans during the initial staging process. Following partial bilateral nephrectomy, histopathological examination revealed renal cell carcinoma (RCC) and oncocytoma in the left and the right kidneys, respectively. Shortly afterwards, lymphoma of the left palatine tonsil was diagnosed and the patient received chemotherapy with rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP regimen), followed by radiotherapy. Due to metastasis of the RCC to the right breast, pancreas and the area of the left psoas major muscle, systemic treatment with pazopanib was commenced. To the best of our knowledge, this is the first reported case of simultaneous diagnosis of non-Hodgkin lymphoma (NHL), RCC and oncocytoma. The aim of this study was to review the related literature, discuss issues regarding the management of this unusual case and identify possible common etiopathological mechanisms underlying the simultaneous occurrence of NHL, RCC and oncocytoma.